2017
DOI: 10.1021/acs.jnatprod.6b00823
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of 2,4-Diacetylphloroglucinol-Producing Pseudomonas and Novel Antiglycation Endophytes from Piper auritum

Abstract: 2,4-Diacetylphloroglucinol (DAPG) (1) is a phenolic polyketide produced by some plant-associated Pseudomonas species, with many biological activities and ecological functions. Here, we aimed at reconstructing the natural history of DAPG using phylogenomics focused at its biosynthetic gene cluster or phl genes. In addition to around 1500 publically available genomes, we obtained and analyzed the sequences of nine novel Pseudomonas endophytes isolated from the antidiabetic medicinal plant Piper auritum. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Although some genera could comprise multiple OTUs that each produce different antifungal compounds, it is likely that some subgeneric OTUs would have the same mechanisms. For example, multiple Pseudomonas species can produce the antifungal compound 2,4-diacetylphloroglucinol ( Gutierrez-Garcia et al, 2017 ). Splitting genera into multiple OTUs may overestimate the diversity of inhibitory mechanisms, so we chose the more conservative approach of leaving genera intact.…”
Section: Methodsmentioning
confidence: 99%
“…Although some genera could comprise multiple OTUs that each produce different antifungal compounds, it is likely that some subgeneric OTUs would have the same mechanisms. For example, multiple Pseudomonas species can produce the antifungal compound 2,4-diacetylphloroglucinol ( Gutierrez-Garcia et al, 2017 ). Splitting genera into multiple OTUs may overestimate the diversity of inhibitory mechanisms, so we chose the more conservative approach of leaving genera intact.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, such a strong phylogenomicdependent GCF pattern of BGC distribution as demonstrated in our study has not been previously reported. Efforts in elucidating BGC diversity had been described through sparse scenarios [6,[102][103][104], while evolutionary interconnections between BGCs and the forces shaping their specialised metabolites are just beginning to be recognized [105]. The postgenomic era has revealed some hypotheses, such as the dynamic chemical matrix evolutionary hypothesis, which reconciles chemical, functional and genetic data [106].…”
Section: Phylogenomic-dependent Patterns Of Nrps Gcfsmentioning
confidence: 99%
“…Control of blast disease employing biological agents can enhance agricultural productivity in crops such as wheat, rice, millet, and barley, and is reported to protect yield loss (Kumar and Kumar, 2011 ; Prajapati et al, 2013 ; Cruz and Valent, 2017 ). Bioinoculants are sustainable natural resources with a wide range of disease control strategies and multiple beneficial plant growth promoting traits (Negi et al, 2015 ; Santhanam et al, 2015 ; Souza et al, 2015 ; Cruz and Valent, 2017 ; Deketelaere et al, 2017 ; GutiéRrez-GarcíA et al, 2017 ). Many studies have reported pseudomonads as bioinoculants with the potential to manage phytopathogens and promote the growth of crops cultivated under different agro-climatic conditions (Yin et al, 2013 ; Selvaraj et al, 2014 ; Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonads are known to produce a wide range of metabolites including antibiotics (2,4-DAPG, HCN, PLT, and PCA) and enzymes that exhibit antagonistic activity against phytopathogens (Jegan, 2015 ; Müller et al, 2016 ; Vacheron et al, 2017 ; Yan et al, 2017 ). A GC/MS profile of MSSRFD41 crude extract showed the presence of reported potential antimicrobial metabolites including pyrrolo [1,2-a] pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl) a major antimicrobial metabolite (Melo et al, 2014 ), H-pyran, 2-(7-heptadecynyloxy)tetrahydro (Devi and Muthu, 2014 ); piperidine-3-carboxylic acid (Santiago et al, 2016 ); tert-hexadecanethiol (Giri et al, 2017 ); 1-heptatriacotanol (Kalaiarasan et al, 2011 ); octadecadienoic acid (Ganesh and Mohankumar, 2017 ); pyrazine and 2,4-DAPG derivatives (GutiéRrez-GarcíA et al, 2017 ). Production of these groups of potential antifungal secondary metabolites correlates to the efficacy of MSSRFD41 in the inhibition of P. grisea .…”
Section: Discussionmentioning
confidence: 99%